2019
DOI: 10.7554/elife.46041
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the rhodopsin-Gαi-βγ complex reveals binding of the rhodopsin C-terminal tail to the gβ subunit

Abstract: One of the largest membrane protein families in eukaryotes are G protein-coupled receptors (GPCRs). GPCRs modulate cell physiology by activating diverse intracellular transducers, prominently heterotrimeric G proteins. The recent surge in structural data has expanded our understanding of GPCR-mediated signal transduction. However, many aspects, including the existence of transient interactions, remain elusive. We present the cryo-EM structure of the light-sensitive GPCR rhodopsin in complex with heterotrimeric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(103 citation statements)
references
References 67 publications
7
94
2
Order By: Relevance
“…The moderate outward displacement of TM6 and the arrangement of Gi relative to CCR5 (Fig. 1A-C) agrees with previous GPCR•Gi complexes (21,22).…”
Section: Overall Structure Of the [6p4]ccl5•ccr5•gi Complexsupporting
confidence: 91%
“…The moderate outward displacement of TM6 and the arrangement of Gi relative to CCR5 (Fig. 1A-C) agrees with previous GPCR•Gi complexes (21,22).…”
Section: Overall Structure Of the [6p4]ccl5•ccr5•gi Complexsupporting
confidence: 91%
“…Studies have suggested that the G βγ subunit of the G i -protein facilitates the coupling of the G αi subunit to the receptor, and the GDP/GTP exchange in the G αi subunit engenders the dissociation and interaction with downstream effectors, such as G αi inhibition of adenylyl cyclase and G βγ activation of ion channels 29,30 . Furthermore, recently solved structure of rhodopsin-G i complex clearly revealed that the interactions between rhodopsin and G i -protein are mainly mediated by the G αi subunit and somewhat by G βγ subunit 14,15,31 . Therefore, we only focused on a variation in the interaction pattern of G αi -protein with CXCR4 receptor to reduce the computing consumption in our systems.…”
Section: Resultsmentioning
confidence: 99%
“…Because the solved crystal structure of CXCR4 (PDB: 3ODU) lacks the N-terminus 4 , which is crucial in the initial binding of CXCL12 to CXCR4 6 , a full-length CXCR4 was constructed by attaching a missing N-terminus (a.a.: 1-26) obtained from the Protein Data Bank (PDB: 2N55) 17 to form a fully modeled CXCR4 containing 327 residues (a.a.: 1-327) according to the method proposed by Lei Xu, et al 7 . First, we superposed the NMR structures of the CXCR4 N-terminus with the CXCR4 N-terminal segment in the crystal structure (residues [27][28][29][30][31][32][33][34][35][36][37][38]. Then, the CXCR4 N-terminal segment (residues 27-38) in the NMR structure was deleted, and the best-oriented N-terminus (a.a.: 1-26) of CXCR4 from the NMR was attached manually to the crystal structure of CXCR4 using the Molecular Operating Environment (MOE) software package MOE2016.08 (http://www.chemcomp.com).…”
Section: Methodsmentioning
confidence: 99%
“…This applies to the recognition of the ligands, but also for the recognition of the signaling transducers (G proteins and arrestins) to a given GPCR, which can be investigated by the same set of methods. How GPCRs select specific transducers remains enigmatic and cannot be firmly predicted from sequence or structural data alone [ 38 , 39 , 40 ]. Instead, the dynamic of the interactions and the existence several intermediate states may drive recognition and activation of the effector [ 19 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%